279 IMPROVING COMPLIANCE FOR RESPIRATORY SYNCYTIAL VIRUS PROPHYLAXIS. (1st January 2006) - Roberts, J. R.; Martines, J.; White, S.; Battaglia, R.; Darden, P. M.
Abstract : Purpose: To evaluate the effectiveness of efforts of the clinic staff to improve palivizumab compliance. Methods: In a hospital-based clinic, a number of changes in procedure for palivizumab injections were instituted for the 2004-2005 RSV season after having a poor rate of kept appointments in the prior year. Changes were as follows: (1) patients received extensive counseling about RSV at the initial visit; (2) the next appointment was made at the time of getting the injection and could be given on any day of the week; (3) a flag system was developed using the electronic medical record so that any other clinic in the MUSC system was alerted to the need that the patient would need palivizumab; (4) reminder phone calls about the appointment the day before; (5) a calendar with a sticker of first appointment and approximate times the next injection was due was given; (6) a tracking chart was placed in the nursing medication room with weight, dosage, and last injection; and (7) staff made presentations to other nursing staff meetings about the new plans, particularly the flag system. Data were examined retrospectively for the year prior to these changes (2003-2004) and for 2004-2005. Outcome measures included the proportion of patients who received the recommended number of shots and the proportion who missed an injection at least 1 month. For the whole sample, we calculated the proportion who met 100% of opportunities for injection (defined as number of shots divided by a visit to an MUSC clinic) and the proportion of "missed opportunities. " A missed opportunity was when the patient presented to clinic for another reason and did not get a shot or simply did not show for their appointment. Comparisons were made between the same variable using chi-square. Results: Palivizumab was given to 24 patients in 2003-2004 and 31 patients in 2004-2005. For the year 2003-2004, 25% received the recommended number of injections. Forty-two percent of patients missed the shot at least 1 month. Seventeen percent made all of the opportunities for injection, and for the sample, there were 45 missed opportunities (35%). For the year 2004-2005, 71% received the recommended number of shots (p = .0005). Thirteen percent of patients missed the shot at least 1 month (p = .01). Seventy-four percent made all of the opportunities for injection (p = .0001), and for the sample, there were 11 missed opportunities (6%; p < .0001). Conclusions: Following a focused effort at improving compliance, a significant number of infants received the appropriate number of palivizumab doses and missed fewer opportunities for injections. Because data were examined retrospectively, the effect of individual interventions cannot be assessed.